Research on the Influence of Confucian Culture on Enterprise Agency Conflicts - Tian, Ran (Transactions on Economics, Business and Management Research, 2023)
With Chinese listed companies from 2008 to 2019 as research samples, this paper takes the number of Confucian academies within a specific radius of the enterprise as the proxy variable of Confucian culture, which found that Confucian culture is negatively correlated with enterprise agency conflicts and can reduce enterprise agency conflicts. Furthermore, the relief effect of Confucian culture on agency conflict is more apparent in private enterprises and areas with high legalization and more openness to the outside world. The conclusion of this paper further enriches the research on the influence of informal institutions on corporate governance, which also provides some reference for regulators when formulating relevant institutions, such as forming an effective mechanism from the perspective of culture, so as to promote the enterprises by cultural restrains. During the promulgation and implementation of legal systems, we should take full advantage of the guiding role of traditional culture and combine formal systems with informal ones, thus leveraging their strengths to promote the healthy development of the market.